No Difference in the Acute Effects of Randomization vs. Blocking of Units of Lower-Extremity Proprioceptive Training on Balance and Postural Control in Young Healthy Male Adults - Ivusza, Patrik; Hortobágyi, Tibor; Sebesi, Balázs; Gáspár, Balázs; Fésüs, Ádám; Varga, Mátyás; Malmos, Vanessza; Váczi, Márk (Frontiers in Physiology, 2022)
Random practice is a form of differential learning and its favorable acute effects on motor performance is are well described when visual tasks are applied in theare practiced process. However, no study to date has investigated the acute effects of differential learning using variable proprioceptive stimuli instead of the visual cues. The aim of the present study was to compare the acute effects of randomized versus blocked lower-extremity proprioceptive training stimuli on balance and postural adjustments. In two conditions, healthy young males (n = 15, age = 23 years) performed 16 one-legged landings on a board the tilt of which could be settilted in four directions: a) tilt direction unknown and randomized and b) tilt direction known and with order of presentation was blocked. Multi-segmental angular sway when while balancing on an unstable surface and postural responses to perturbation stimulus by surface tilts, were measured before and four minutes after training. Overall frontal-plane postural sway on the unstable surface decreased (p < 0.05, η2 = 0.022) in both conditions, while sagittal-plane postural sway remained unchanged. When the surface was toes-up tilted in the perturbation test, the sagittal-plane shank-thigh-pelvis alignment improved in both conditions (p < 0.05, η2 = 0.017), but the direction of the segmental positioning was non-uniform across participants. We conclude that there were no differences in the acute effects of randomization vs. blocking of units of lower-extremity proprioceptive training on did not affect balance and postural control in our cohort of healthy young adults but the improvements weare test-specific.